(untitled) (World Science, 2023)
Active thunderstorm activity is dangerous for various sectors of the economy, and especially for aviation flights. The study determined the modern spatio-temporal distribution of thunderstorm activity at meteorological stations of the Odesa region for 2005–2022, as well as the circulation and thermodynamic conditions of thunderstorm formation. Revealed that thunderstorm activity in 2005-2022 at the stations of Odesa region was less active compared to 1961-1990, but the geographic distribution of the intensity of thunderstorm formation did not change. Almost all thunderstorms formed from April to October. The maximum annual variation over the entire region occurred in June, the minimum in January. May and June 2013 and June 2021 were marked by the most active thunderstorm formation. Exposed that in 2018-2022 intra-mass thunderstorms and thunderstorms on the main cold fronts formed more often over Odesa. Most often, before the storm in the Whiting and Total Totals indices reached critical criteria.